2014
DOI: 10.1039/c4ta01384k
|View full text |Cite
|
Sign up to set email alerts
|

A new class of solid Lewis acid catalysts based on interlayer expansion of layered silicates of the RUB-36 type with heteroatoms

Abstract: Interlayer expansion of the layered zeolite precursor RUB-36 in presence of an Fe source simultaneously achieved the expansion and the introduction of catalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…Derivatives of 2D layers with the CDO zeolite topology are currently being explored. As shown in Table 3, interlayer-expansion by the silyation [115,116,118,119,125] and pillaring [33] of PLS-1 has led to COD zeolites with expanded and pillared structures.…”
Section: D Layers With 8-mr Zeolite (Cas Cdo Mtf Nsi Rth Rwr) Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Derivatives of 2D layers with the CDO zeolite topology are currently being explored. As shown in Table 3, interlayer-expansion by the silyation [115,116,118,119,125] and pillaring [33] of PLS-1 has led to COD zeolites with expanded and pillared structures.…”
Section: D Layers With 8-mr Zeolite (Cas Cdo Mtf Nsi Rth Rwr) Tmentioning
confidence: 99%
“…Materials 2020, 13, 1822 11 of 52 [115,116,118,119,125] and pillaring [33] of PLS-1 has led to COD zeolites with expanded and pillared structures. HPM (nanostructured hybrid biohybrid and porous materials)-2 is a new layered organosilicate containing 2D layers with an MTF topology, yielding zeolite MTF by calcination [100].…”
Section: D Layers With 8-mr Zeolite (Cas Cdo Mtf Nsi Rth Rwr) Tmentioning
confidence: 99%
“…Recently, it has also been shown to be possible to introduce catalytic activity in the pillars. 32 , 33 Excellent reviews of the above strategies are available. 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
“…In explorative studies, it could be shown that other, functionalized linker groups can be inserted and that by increasing the linker dimensions, the pore size could be expanded [ 48 -50 ]. The latest Rietveld analysis of an IEZ material showed that using Fe 3+ in aqueous solution as linker species, a microporous, metal-expanded, thermally stable silicate framework could be formed exposing the reactive metal linker site to the pore space [ 51 ]. The direction of an active component on a specifi c framework site is demonstrated with the concept of interlayer expanded zeolites and proven based on various structure analyses.…”
Section: Data Mining: Generating a Starting Structure Model On The Bamentioning
confidence: 98%